New Orleans and the Mississippi river : a braudelian time-geographic perspective - Kent Mathewson (Confins)
The site and situation of New Orleans, entrepôt city on the Mississippi River, North America’s major fluvial system, presents an ideal case for applying what I have termed the “Braudelian time-geographic” perspective. Since its founding in the early 1700s, New Orleans and the Mississippi River have been integrally connected. But the relationship has been variable. Much of this variation stems from New Orleans’ larger connections with its hinterlands – one upriver a half a continent in extent, and the other down river and into the Gulf/Caribbean Basin and rimlands. This paper charts key shifts in city/river relations using a Braudel’s fifty-year, or conjunctural interval of historical change. The paper also applies Torsten Hägerstrand’s concept of time-geography to New Orleans as an urban organism, with a life of its own, but always mediated by the Mississippi.